Identification of Benefits of Participating in Content Mastery Services at SMPN 37 Muaro Jambi - Khofifah Indrayani; Angga Pratama (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to identify the benefits of participating in content mastery services in terms of attitudes and study habits, learning techniques/learning methods, and educational planning. Content mastery services in junior high schools are core activities supporting the implementation of the content mastery service process. Methodology: The population in this study were all students at SMP Negeri 37 Muaro Jambi with a total of 38 students. This research is a population research because all members of the population are the research samples. Data in this study were collected through a questionnaire with a dichotomous scale and processed using a percentage formula. Main Findings: The results of the study showed that (1) Identification of the benefits of participating in content mastery services related to attitudes and study habits at SMP Negeri 37 Muaro Jambi was at good quality (76.9%) meaning that attitudes and study habits were good. (2) Identification of the benefits of participating in content mastery services for indicators of learning techniques / learning methods at SMP Negeri 37 Muaro Jambi that are related to being of good quality (75.6%) meaning that learning techniques / learning methods are good, and (3) Identification of the benefits of participating in services mastery of the related educational planning indicator content at SMP Negeri 37 Muaro Jambi is of good quality (81%) meaning that planning for education is good. The implications of the research results for guidance and counseling services can be carried out in the following steps: (1) Help develop a classroom atmosphere, teacher-student relationships and student-student relationships that support the implementation of guidance and counseling. (2) Providing opportunities and facilities for students who need guidance and counseling services/activities to participate/undergo the intended services/activities. (3) Participate in special activities for handling student problems, such as case conferences, and (4) Assist in gathering information in the context of evaluating guidance and counseling services and follow-up efforts. Novelty/Originality of this study: Knowing the benefits of participating in content mastery services in terms of attitudes and study habits, learning techniques/learning methods, and educational planning.